2022
DOI: 10.1007/s13399-022-02428-x
|View full text |Cite
|
Sign up to set email alerts
|

Manure biostabilization by effective microorganisms as a way to improve its agronomic value

Abstract: The traditional logic behind effective microorganism is based on a media inoculation with mixed cultures of beneficial microorganisms to create a more favorable environment for plant growth and health when the media is the soil. Following this rationale, other research works have been focused on studying the effect of effective microorganisms when they are used as manure stabilizing agents, in some cases by including them in animal diets, reporting, in all cases, beneficial properties. However, the use of effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 91 publications
0
7
0
1
Order By: Relevance
“…Therefore, the molecular taxonomy and genome sequencing of LAB strains become an effective method for identifying species levels. Lactobacillus plantarum , L. casei , Lactococcus , Bifidobacterium , and Streptococcus lactis are isolated from the intestinal tract of animals and fermented food [ 22 ]. L. acetotolerans , L. pontis , and L. suebicus species show high survival rates in the cow gut [ 23 ].…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the molecular taxonomy and genome sequencing of LAB strains become an effective method for identifying species levels. Lactobacillus plantarum , L. casei , Lactococcus , Bifidobacterium , and Streptococcus lactis are isolated from the intestinal tract of animals and fermented food [ 22 ]. L. acetotolerans , L. pontis , and L. suebicus species show high survival rates in the cow gut [ 23 ].…”
Section: Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…In this context, farmyard manure and plant-based compost is integral to organic farming and sustainable agriculture. LAB decompose and bio-stabilize the animal and plant waste to improve the agronomic value and assimilate organic matter such as lignin and cellulose materials [ 22 ]. Wang et al, found that Bacillus stearothermophilus elevate the relative abundance of LAB strains in soil [ 122 ].…”
Section: Biofertilizer Of Labmentioning
confidence: 99%
“…to meet the nutritional needs of plants and to reduce the proportion of disease-causing microorganisms. In addition to metabolizing organic compounds, EMs produce simple plant compounds that, when added to the soil, improve their use in agriculture and stabilise the natural ecosystem (Hidalgo et al, 2022;Rastogi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This effect on ammonia is presumably caused by ammonia adsorption by the aluminosilicates as well as adsorption by carboxyl compounds, phenols, and lactones present on the biochar surface, in addition to changes in the gut microbiome due to biochar supplementation [ 19 , 20 ]. Another approach to ammonia control is to utilize effective microorganisms either as feed additives or additives to the environment, such as bacteria from the nitrogen-fixing genera Rhizobium , Azotobacter, Azospirillum, Beijerinckia, Azoarcus, Burkholderia, Enterobacter, Klebsiella, and Bacillus [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%